The valley of the shadow [large type] : a Cornish mystery - Dunn, Carola (Dunn, Carola. Cornish mysteries., 2013)
While out on a walk, Eleanor Trewynn, her niece, and her neighbor spot a young, half-drowned Indian man floating in the water. Delirious and concussed, he utters a cryptic message about his family being trapped in a cave and his mother dying. The young man is whisked away to a hospital, and a desperate effort is mounted to find the missing family - who the local police inspector presumes are refugees from East Africa abandoned by a smuggler.